2014
DOI: 10.1007/s10142-014-0420-1
|View full text |Cite
|
Sign up to set email alerts
|

Genes regulating lipid and protein metabolism are highly expressed in mammary gland of lactating dairy goats

Abstract: Dairy goats serve as an important source of milk and also fulfill agricultural and economic roles in developing countries. Understanding the genetic background of goat mammary gland is important for research on the regulatory mechanisms controlling tissue function and the synthesis of milk components. We collected tissue at four different stages of goat mammary gland development and generated approximately 25 GB of data from Illumina de novo RNA sequencing. The combined reads were assembled into 51,361 unigene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
50
0
9

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(71 citation statements)
references
References 70 publications
12
50
0
9
Order By: Relevance
“…As expected, the RNA expressions of the factors involved in the PI3K/Akt/mTOR signaling pathway at peak milk stage were higher than that in the dry period stage, which was consistent with previous investigations in mammary tissues 2426 . Interestingly, the expression of MEN1 /Menin showed an opposite change at both the RNA and protein level.…”
Section: Discussionsupporting
confidence: 92%
“…As expected, the RNA expressions of the factors involved in the PI3K/Akt/mTOR signaling pathway at peak milk stage were higher than that in the dry period stage, which was consistent with previous investigations in mammary tissues 2426 . Interestingly, the expression of MEN1 /Menin showed an opposite change at both the RNA and protein level.…”
Section: Discussionsupporting
confidence: 92%
“…The high expression of casein ( CN ) genes, all increasing in expression from D1 to D2 lactation stages, was not surprising because caseins, together with the whey proteins, represent the 90% of milk proteins fraction [67]. In this work, we found that CSN2 and the whey protein α-lactalbumin (α-LA) coding gene ( LALBA ) have the highest expression values, as already detected by [61] in goat, [33] in cow and [507] in human.…”
Section: Discussionsupporting
confidence: 68%
“…Considering the de novo assembly approach we compared our results with a similar study on goat mammary gland in which 98,864 transcripts and 51, 361 unigenes with a mean length of 1,219 bp were obtained [61]. Numbers are comparable, even if smaller, to those obtained by us.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…Gene expression abundance analysis: Based on the data obtained from the sequencing, the dairy goat mammary transcriptome data obtained by 52 were used as reference sequences. Using the software bowtie 0.12.8, gene expression was measured based on the RPKM (Reads Per Kilobase of exon model per Million mapped reads) value (S2).…”
Section: Animals and Samples Of Rna Extractionmentioning
confidence: 99%